Penerapan Metode MFEP Berbasis Web Pada Sistem Pendukung Keputusan Penilaian Kompetensi Soft Skill Pegawai - Melly Ega Fitria; Mohd Siddik; Suparmadi Suparmadi (Building of Informatics, Technology and Science (BITS), 2022)
An agency cannot be separated from the role of human resources (HR) who work in it. The quality of human resources is one of the factors to increase the productivity of an agency's performance. Human resources are the most important contribution to the growth and development of the agency. Therefore, an agency needs to conduct an employee performance assessment to determine the success or failure of the employee in carrying out his duties. Soft skill competency assessment is a very important issue in managing employee performance. The system that runs at the Subur Village Hall Office in assessing employee soft skill competencies has weaknesses, namely the employee assessment process is still done manually and the data processing process has not used an application program. In addition, the assessment is still subjective and not relevant to the actual situation, so it cannot be used as a basis for objective decision making so that it is difficult to determine the soft skill competency assessment possessed by employees. The purpose of this study is to assist the agency in assessing employee performance quickly and accurately. The research was conducted using qualitative methods with program design using the multi-factor evaluation process (MFEP) method. The results of testing the MFEP method calculation system are close to the results of calculations carried out by the Subur Village Hall Office using the Microsoft Excel application according to the weights on each criterion that have been determined by the Subur Village Hall Office